Upaya Penyelesaian Konflik Komunikasi Interpersonal Dalam Dinamika Organisasi LDK Syahid FDIKOM di UIN Jakarta - Nasichah; Eka Nia Wulandari; Mayla Zahwa Syahbaniah (CV. ITTC INDONESIA, 2024)
Interpersonal communication conflict is a common issue, particularly between individuals. The aim of this study is to identify and analyze efforts to resolve interpersonal communication conflicts within the Dakwah Campus Organization (LDK) Syahid at FDIKOM UIN Syarif Hidayatullah Jakarta. Through in-depth interviews conducted on July 8, 2024, with the Chairman (Adrian Putra Prabowo) and two organization members (Salman and Galih), the research found that the primary strategies used to address conflicts were open discussions and consensus-building. Additionally, enhancing communication skills through training and workshops, along with reinforcing organizational values, played pivotal roles in conflict management. Established on May 28, 1996, LDK Syahid engages in various activities aimed at developing leadership qualities and enhancing member capabilities. The study's findings underscore that an approach emphasizing dialogue, communication training, and organizational values effectively resolves interpersonal communication conflicts, fostering a conducive environment for collaboration and enhancing organizational productivity